Oczny zespół maskujący w przebiegu przewlekłej białaczki limfocytowej - Kubicka-Trząska, Agnieszka; Gedliczka, Monika; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To report a rare case of a masquerading syndrome in a course of chronic lymphocytic leukemia (CLL). Material and methods: A 57 years old woman with bilateral lacrimal glands enlargement and chronic uveitis unresponsive to local steroids, was studied. Patient’s general history was positive for chronic lymphocytic leukemia, B cell (B-CLL); actually remission. The patient underwent complete ophthalmic examination with additional A and B-scan ultrasonography (USG), computed tomography (CT) and nuclear magnetic resonance (NMR) imaging of orbital cavities and also biopsy of both lacrimal glands was performed. Results: USG, CT and NMR scans revealed the intraocular inflammation and inflammatory enlargement of both lacrimal glands. The histopathological examination of lacrimal glands showed the presence of lymphocytic infiltrations within the glands’ tissue. The patient started with chemotherapy: Fludarabin and Cyclophosphamide. Within weeks the intraocular inflammation was under control and the resolution of lacrimal glands edema was noted. Conclusions: Malignancy should be considered in cases of chronic uveitis that do not respond to steroid therapy. Chronic lymphocytic leukemia rarely masks as chronic intraocular inflammation, in a sporadic cases however it may herald the relapse of the disease.